Determinação das propriedades de tração de compósitos de matriz epóxi reforçados com fibra de Guarumã - PINHEIRO, Miriane Alexandrino (2018)
The need to develop materials with differentiated properties, such as good mechanical performance, low cost and environmentally correct, has increased every day. In this context, we highlight the search for the development of polymeric matrix composites with natural fiber reinforcement. These fibers have advantages over synthetic fibers because they are found in large quantities and with ease, as is the case of guarumã (Ischinosiphon koern), an abundant species in the region of floodplains. In this work, epoxy matrix composites reinforced with guarumã fibers were analyzed mechanically and microstructurally. The composite materials manufacturing process started with the characterization of the fibers. The test specimens were produced in silicon molds and sanded to meet the specifications of ASTM D 638, in order to carry out the tensile strength tests, and later the scanning electron microscopy, to analyze the microstructure of the fractured material. From the values obtained after the tensile test, it was observed that, despite the low mechanical performance when related to the matrix, the addition of guarumã fibers tends to a slight reinforcement in the epoxy matrix. The microstructural characterization revealed that the epoxy matrix composites reinforced with guarumã fibers have a great potential when compared to composites that have other natural fibers as reinforcement.